Effect of surfactant and electron treatment on the electrical and thermal conductivity as well as thermal and mechanical properties of ethylene vinyl acetate/expanded graphite composites. Issue 32 (14th May 2015) - Sefadi, Jeremia Shale; Luyt, Adriaan Stephanus; Pionteck, Jürgen; Piana, Francesco; Gohs, Uwe
ABSTRACT This study presents an investigation of the electrical and thermal conductivities of composites based on an ethylene vinyl acetate (EVA) copolymer matrix and nanostructured expanded graphite (EG). To improve the EG dispersion in EVA, EG sheets were modified by treating them with the anionic surfactant sodium dodecyl sulphate (SDS) in water. The modified SDS‐EG platelets, after being filtered and dried, were melt‐mixed with EVA to prepare the composites. Finally, both EVA/EG and EVA/SDS‐EG composites were subjected to 50 kGy electron beam (EB) irradiation. SEM images confirm that the irradiated EVA/EG samples had improved interfacial adhesion, while the irradiated EVA/SDS‐EG samples showed even better interfacial adhesion. The gel contents of the irradiated samples without and with SDS treatment increased with increase in EG loading. The EVA/EG composites exhibited a sharp transition from an insulator to a conductor at an electrical percolation threshold of 8 wt %, but with SDS‐EG the electrical conductivity was extremely low, showing no percolation up to 10 wt % of filler. The EB irradiation had no influence on electrical conductivity. The thermal conductivity linearly increased with EG content, and this increase was more pronounced in the case of SDS‐EG, but decreased after EB irradiation. The thermal properties were little influenced by EB irradiation, while better polymer–filler interaction and better filler dispersion as a result of SDS treatment, and the EB irradiation initiated formation of a cross‐linked network, had a positive effect on the tensile properties. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 42396.